The Valuation Relevance of Reversing Deferred Tax Liabilities - Guenther, David A.; Sansing, Richard C. (The Accounting Review, 2004)
This paper compares two attributes of a deferred tax liability (DTL) that arise from differences in book and tax depreciation methods. The first attribute is the effect of the DTL on the market value of the firm. The second is the length of time between when the asset is placed into service and when the DTL associated with that asset begins to reverse. The paper shows that a decrease in the time it takes for the DTL to begin to reverse is neither necessary nor sufficient for the value of the DTL to increase. It also shows that the value of the DTL is not equal to the present value of the future deferred tax expense. The effect of one dollar of DTL on firm value depends only on the tax depreciation rate and the discount rate.